Endothelial Cell Activation and Thrombin Generation Assessment for the Risk of Severe Early Onset Preeclampsia. the ROADMAP-EOP Study. (November 2022) - Van Dreden, Patrick; Lefkou, Eleftheria; Ka, Aboubakar; Sfakianoudis, Konstantinos; Rousseau, Aurélie; Grusse, Matthieu; Elalamy, Ismail; Gerotziafas, Grigoris T
Background: The ROADMAP-EOP study aimed to identify clinically relevant biomarkers of hypercoagulability for the identification of pregnant women at risk of early onset preeclampsia worsening. Methods: The ROADMAP-EOP observational single center retrospective case–control study was conducted in Greece (Centre for Human Reproduction, Genesis Athens Clinic, Athens, Greece) from July 2020 to July and enrolled pregnant women diagnosed with EOP stratified in mild EOP group (n = 34) and severe EOP group (n = 15) as well as women with uncomplicated pregnancy (control group; n = 35). All women were assessed with thromboelastometry (ROTEM®), Calibrated Automated Thrombogram®, tissue factor activity (TFa), procoagulant phospholipid dependentclotting time (Procoag-PPL®), Proteins S (PS), TFPI, D-dimer, antithrombin (AT), thrombomodulin (TM), fibrinogen, prothrombin time (PT) and activated partial thromboplastin time (aPTT). The primary study end-point was severe earlyonset preeclampsia. Principal component analysis (PCA) was performed. Results: The PCA analysis showed that a score composed of the lag-time, ttPeak and Procoag-PPL accurately predicted severe EOP (sensitivity 71.4%, specificity 61.8%, and AUC of the ROC analysis 0.953). Conclusion: The pilot ROADMAP-EOP shows that activation of endothelial cells and blood hypercoagulability are driven events in the worsening of EOP. Among a large panel of biomarkers and coagulation assays, thrombingeneration test and procoagulant phospholipid dependent clotting time emerged as clinically relevant for the evaluation of the risk of severe EOP. This methodology for the development of a new clinic-biological risk assessment model for prompt identification of pregnant women at risk of severe EOP must be validated in a large multi-centerprospective study.